AMELİYAT SONRASI PELVİK IŞINLAMALARDA İNCE BAĞIRSAKLARI RADYASYONDAN KORUMAK AMACIYLA KULLANILAN ÜÇ ADET SENTETİK GREFTİN SONUÇLARININ SIÇAN MODELİNDE KARŞILAŞTIRILMASI - GÜLER, Emel; ERTÜRK, Süphan; ERSAN, Yılmaz; YÜCEYAR, Serdar; ÇİÇEK, Yusuf; EREN, Deniz; BALCI, Huriye; UZEL, Ömer; ERDAMAR, Sibel; DİRİCAN, Ahmet (Cerrahpaşa Medical Journal, 2019)
Background and Design.- To compare the effectiveness of pelvic mesh sling method with three different types of mesh in prevention of postoperative radiation hazard of small intestines in rats. Fifty Wistar albino rats were allocated into 5 groups. Group I and II were assigned as control group and radiation group, respectively. In groups III, IV and V, Gore-tex (PTFE=polytetrafluoroethylene), Parietex composite (polyester) and Vicryl (polyglactin 910) meshes were used before pelvic radiation, respectively. The comparison of the meshes were made by the assessment of blood levels of vitamin B12, folic acid, total protein, albumin, total cholesterol, and observation of adhesion formation as well as histopathological examination of the small intestines. Results.- Radiation interfered with absorption of vitamin B12 and folic acid but Gore-tex and Parietex composite meshes had significant protective effect. Similarly, radiation caused significant decrease in blood cholesterol level. On the other hand, blood cholesterol level was found within normal limits only in Parietex composite mesh group. All of the meshes caused adhesion formation with a decreasing order of Gore-tex, Parietex composite and Vicryl meshes. However, only the degree of adhesions in Gore-tex mesh group was statistically significant. Conclusion.- In the present study it was found that the most effective mesh against postoperative radiation hazard after pelvic radiation was Parietex composite mesh. Yet, further long term studies are required to determine the ideal mesh in protecting small intestines from postoperative radiation hazards.